2004
DOI: 10.1529/biophysj.103.035717
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine Membrane Compartments for Molecular Diffusion as Revealed by Single Molecule Techniques

Abstract: Plasma membrane compartments, delimited by transmembrane proteins anchored to the membrane skeleton (anchored-protein picket model), would provide the membrane with fundamental mosaicism because they would affect the movement of practically all molecules incorporated in the cell membrane. Understanding such basic compartmentalized structures of the cell membrane is critical for further studies of a variety of membrane functions. Here, using both high temporal-resolution single particle tracking and single fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

60
554
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 408 publications
(621 citation statements)
references
References 48 publications
60
554
7
Order By: Relevance
“…Moreover, in different systems using different tracking techniques, similar observations were made [50][51][52][53]. Frick et al [54] have recently given additional evidence supporting the previous interpretation by using FRAP on four different proteins.…”
Section: Interacting Brownian Particle Modelsupporting
confidence: 57%
See 1 more Smart Citation
“…Moreover, in different systems using different tracking techniques, similar observations were made [50][51][52][53]. Frick et al [54] have recently given additional evidence supporting the previous interpretation by using FRAP on four different proteins.…”
Section: Interacting Brownian Particle Modelsupporting
confidence: 57%
“…As a consequence, assuming that the number of proteins within an assembly is constant, both the microscopic and macroscopic diffusion coefficients remain proportional to L 2 [15]. 40 J Chem Biol (2008) 1:37-48 Moreover, in different systems using different tracking techniques, similar observations were made [50][51][52][53]. Frick et al [54] have recently given additional evidence supporting the previous interpretation by using FRAP on four different proteins.…”
mentioning
confidence: 78%
“…• Kusumi and colleagues have shown that the plasma membrane is compartmentalized by a picket fence of transmembrane proteins that are anchored to the submembrane actin cytoskeleton 26,[67][68][69] . The fence allows relative free lateral diffusion of lipids within compartments but restricts movement between compartments.…”
Section: Box 3 Extrapolating From Model Membranes To the Plasma Membranementioning
confidence: 99%
“…Five and 2 µm signal were separately input into the piezo, and the recovered motions were within 4% of expected value. 4.13E−10, 4.33E−10, and 4.53E−10 cm 2 /s, for the individual x, y, and z axes, respectively and 4.30E−10 cm 2 /s for the overall diffusion coefficient. Figure 4c and d shows an example of diffusion with flow.…”
Section: Free Diffusionmentioning
confidence: 99%
“…The technique was extended by using video microscopy and small gold particles (20-40 nm) as the label for the particle of interest [2]. Other groups investigated lipid motion using a high speed video camera and obtained a frequency response of 40 kHz and a precision of 17 nm [3,4]. Kis-Petikova developed a technique to track particles in 2D using the two-photon microscope [5].…”
Section: Introductionmentioning
confidence: 99%